EFEKTIFITAS PROGRAM INTERVENSI ANEMIA ZAT BESI PADA IBU HAMIL BERBASIS MASYARAKAT: SYSTEMATIC REVIEW - Anak Agung Ngurah Kusumajaya (Poltekkes Kemenkes Denpasar, 2017)
Anemia in pregnant women is a serious problem and determines the health of mother and child, so it is necessary to take preventive interventions. The purpose of this systematic review was to compare the effectiveness of intervention programs maternal anemia iron-based society, especially in developing countries. A major focus of study materials was the effectiveness of iron tablets, folic acid or multiple micronutrient another in pregnant women with and without iron-deficiency anemia. Information from various articles related to the topic was collected using three sources, namely database Pubmed (Medline), ProQuest and Ebsco (CINAHL Plus with Full Text) in the time range of 2010 to 2015. A total of nine research articles intervention iron anemia in pregnant women based society in developing countries were reviewed, of which five articles focus on interventions related to its effectiveness in pregnant women who are anemic, three articles are nutrition intervention programs anemia in pregnant women non anemia / anemia light, and one article relating to the use of supplements regularly or irregularly. Results of the review showed that the effectiveness of intervention programs iron anemia need to be adjusted to the target pregnant woman. Intervention programs and the provision of iron tablets not regularly every day provide protective effects in pregnant women who are not anemic. Intervention program of tablet combination of iron, folic acid or multiple micro-nutrients need to be given to pregnant woman with anemia or in the region with a medium or high prevalence of anemia in pregnant mothers, and feeding every day during the last trimester of pregnancy. Program interventions are integrated with the increase in food consumption and iron tablets adherence could provide optimal impact.Key words: anemia, iron tablet, pregnant woman, and intervention